THE PROBLEM OF DETERMINING THE LENGTH OF THE ZONES H-CHARACTERISTICS IN CALCULATING THE RELIABILITY OF TECHNICAL OBJECTS - Laguta, V. V.; Kapitsa, M. I. (Science and Transport Progress, 2008)
Setting up a problem of determination of the zone lengths of a failure function is considered in the paper. Properties of a failure function and an intensity failure function are taken into consideration. The problem statement has been formulated as a structure definition problem.